Social Education in Europe and Costa Rica. Merton´s latent functions in public social intervention services (Revista ABRA, 2020)
The functionalist or utilitarian paradigm, despite the critics received, is still in force in the current situation of social sciences. Robert K. Merton, among his contributions to functionalism, conceptualizes as manifest functions the observed and objective consequences which are searched for and recognized. He names latent functions those which are not. This distinction can provide with a methodological way for the functional analysis of our social institutions and lead us towards the observation and later study of their latent functions. Social Education is a profession and intervention methodology in social context. Starting from its manifest functions, a proposal is made to analyze the possible latent functions of the public institutions where it is carried out.